‘The lights are on, and the doors are always open’: a qualitative study to understand challenges underlying the need for emergency care in people experiencing homelessness in rural and coastal North East England - Sheena E Ramsay; Eileen Kaner; Jill Harland; Emma A Adams; Deepti A John; Steven A Thirkle (BMJ Public Health)
Introduction People experiencing homelessness have high rates of emergency care attendance compared with the general population. This study explores the factors underlying the need for emergency care services among people experiencing homelessness in rural and coastal areas of North East England.Methods The study was conducted in Northumberland and North Tyneside (North East England). One-to-one semistructured interviews were conducted with people experiencing homelessness. Interviews and focus groups were undertaken with frontline staff from housing associations, police, ambulance services, emergency care, primary healthcare, mental health services and alcohol and drug recovery services. Discussions centred on emergency care experiences, reasons for access and underlying health and social needs.Results Participants included 20 people experiencing homelessness (aged 18–56, 70% male) and 18 service professionals (aged 20–56, 56% female). Emergency care was often viewed by participants as an accessible safe place. Four key themes were found in this rural and coastal context: accessibility challenges due to limited public transport and geographic isolation; fragmented support exacerbated by widely dispersed services; service restrictions and limited alternatives having particular impact where options are few and prioritisation of immediate needs influenced by limited local resources.Conclusion Challenges in accessing primary healthcare and social care, alongside varying levels of timely support and understanding of individual contexts, can contribute to the increased use of emergency care for people experiencing homelessness in rural and coastal areas. Integrating services with a focus on flexibility could be crucial for addressing the needs of these populations. This involves adapting to the unique circumstances of multiple deprived groups who lack access to community support.